From mediated listening to creative listening - Iazzetta, Fernando (2012)
Listening is a relatively recent concern in the context of musical studies. With the advent of the phonography in the late nineteenth century there was a significant change in the relationship between music making and its reception. Attention turns to the processes of listening as they become increasingly mediated by audio technologies. A listening situation mediated by different devices raises the listener to the condition of an expert in the act of listening. At same time she moves away from the exercise of musical practice. Digital network technologies add a new perspective to the listener’s role who subverts the devices created for reproduce music into devices to (re)create music.